DEVELOPING MATHEMATICS LEARNING EQUIPMENT USING INVESTIGATION APPROACH FOR JUNIOR HIGH SCHOOL STUDENT GRADE IX AT CURVED SURFACE SOLID MATERIAL. - Nasrullah Aldiawan; Sugiyono . (Jurnal Pedagogi Matematika, 2017)
The research aim is to descript the quality of Mathematics Learning Equipment using investigation approach for junior  high  school  student  gader  IX  at  curved surface  solid material.  This  is  a  RD  research  using  ADDIE development  model  which  consists  of  five  steps  i.e.  Analysis,  Design,  Development,  Implementation,  and Evaluation. Research  instruments  consist  of assessment  sheet  (for lesson  plan and  student worksheet), students’ response  questionnaire,  and  student  test  sheet.  Implementation  step  in  this  research  was  held  in  SMP N  1 Kalikotes, Klaten. The number of lesson plan and student worksheet developed in this research is six each. The learning equipment fulfill valid criteria by assessment from validators which scoring 3,52; 3,73; 3,65 in scale of 5. 75% students pass the student test with the average score was 72,64 which means the learning equipment meets effective  criteria.  Students’ response  questionnaire  scored  4,26  average  in  scale  of  5 which  means  the  students worksheet fulfill very practical criteria.